2006
DOI: 10.1080/15226510600992808
|View full text |Cite
|
Sign up to set email alerts
|

Potential of vetiver (Vetiveria zizanioides(L.) Nash) for phytoremediation of petroleum hydrocarbon-contaminated soils in Venezuela

Abstract: Venezuela is one of the largest oil producers in the world. For the rehabilitation of oil-contaminated sites, phytoremediation represents a promising technology whereby plants are used to enhance biodegradation processes in soil. A greenhouse study was conducted to determine the tolerance of vetiver (Vetiveria zizanioides (L.) Nash) to a Venezuelan heavy crude oil in soil. Additionally, the plant's potential for stimulating the biodegradation processes of petroleum hydrocarbons was tested under the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 14 publications
2
54
0
4
Order By: Relevance
“…(Poaceae), respectively. Brandt et al (2006) found evidence that the reduced growth and biomass found in Vetiveria zizanioides (L.) Nash (Poaceae) in the contaminated soil was related to the nutrients content. Daniel-Kalio and Pepple (2006) found that the time interval between the contamination and the establishment of seedlings affected the biomass of Commelina benghalensis L. (Commelinaceae).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(Poaceae), respectively. Brandt et al (2006) found evidence that the reduced growth and biomass found in Vetiveria zizanioides (L.) Nash (Poaceae) in the contaminated soil was related to the nutrients content. Daniel-Kalio and Pepple (2006) found that the time interval between the contamination and the establishment of seedlings affected the biomass of Commelina benghalensis L. (Commelinaceae).…”
Section: Discussionmentioning
confidence: 98%
“…The same substance can induce different effects in different species, and conversely, the same symptoms can arise from exposure to different substances (Baker, 1970). The most common and important symptoms observed in the plants contaminated with oil and its byproducts include the erosion of the epicuticular wax (Baker, 1970), degradation of chlorophyll (Baker, 1970;Malallah et al, 1996 and, alterations in the stomatal mechanism (Baker, 1970), reduction in photosynthesis and respiration (Baker, 1970), increase in the production of stress-related phytohormones (Larcher, 2000), accumulation of toxic substances or their byproducts in vegetal tissue (Baker, 1970), decrease in size and less production of biomass (Proffitt et al, 1995;Green et al, 1996;Kuhn et al, 1998;Brandt et al, 2006;Daniel-Kalio and Pepple, 2006;Adenipekun et al, 2008). In some cases after an oil spill, an increase in the production of biomass and in the growth and development of some species can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…The roots serve the dual purpose of sustaining the environment as they form an intertwined network in the soil, making the soil environment suitable for land rehabilitation. Vetiver roots are also known to regulate soil and water conservation and remediate polluted sites (Brandt et al, 2006;Antiochia et al, 2007). Moreover, the roots of vetiver also synthesize a specific essential oil (EO), which is highly valued for its aromatic and pharmaceutical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Also Chang and Richard (1998) have reported enhanced oil remediation by addition of bulking agent. Brandt et al (2006) during their research carried out on phytoremediation of petroleum contamination found that Vetiver was efficient in degrading the contaminant. This study resulted in degradation of oil and TPH compounds by using all possible technologies implemented till date by making use of plant (phytoremediation), microbial consortium (bioremediation), addition of bulking agent and nutrient (biostimulation) together, and hence has proved its efficiency over conventional remediation technologies.…”
Section: T3 [B]: Effect Of Bioaugmentation Biostimulation Phytoremementioning
confidence: 99%
“…3). Brandt et al (2006) has mentioned in his study that petroleum hydrocarbons have high carbon content but poor nitrogen and phosphorus content, and microbes use up the available nutrients during mineralization of hydrocarbons. Hence, supplementation of nutrients helps in increasing the degradation rate.…”
Section: T2 [B]: Effect Of Phytoremediation and Biostimulationmentioning
confidence: 99%